PELATIHAN EMOTIONAL INTELLIGENT UNTUK MENINGKATKAN SERVICE QUALITY PADA FRONTLINER DI SALAH SATU PERGURUAN TINGGI SWASTA - Widodo, Mochamad Sigit; Hariyanto, Heru (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
Service Quality is an important asset for higher education institutions, because this Service Quality can have the most important impact on service recipient satisfaction, and finally if service satisfaction occurs repeatedly, customer loyalty or customer satisfaction is formed (Tjiptono, 2008). The implementation of Service Quality by the right service provider (fronliner) will be able to provide satisfaction. Therefore, there is a need for Emotional Intelligent training to improve Service Quality at the frontliner of one of the private universities in Surabaya. Participants in the